Dynamic perforation of lightweight armor: Temperature-dependent plasticity and fracture of aluminum 7020-T6. (October 2020) - Roth, Christian C.; Fras, Teresa; Mohr, Dirk
Highlights: Completed comprehensive experimental program plasticity and fracture of aluminum 7020-T6. Used Yld2000–3d plasticity model with rate-independent, but temperature-dependent Swift-Voce hardening. Obtained reasonable fracture predictions with a rate- and temperature-independent Hosford-Coulomb model. Performed impact experiments on 4 mm thick targets with blunt, hemispherical and conical steel projectiles. FE model correctly predicts differences in perforation mechanism and ballistic limit. Abstract: The design of armored vehicles requires reliable constitutive models that are valid over a wide range of strain rates and temperatures. A comprehensive experimental program is executed to characterize the stress-strain response of high strength aluminum 7020-T6 at temperatures ranging from 20°C to 320°C. It includes tensile experiments on uniaxial, notched, central hole and shear specimens. Aside from low and intermediate strain rate experiments, high strain rate experiments are performed on a Split Hopkinson Pressure Bar (SHPB) system equipped with a load inversion device. Furthermore, hemispherical punch and V-bending experiments are performed to achieve equi-biaxial tension and transverse plane strain conditions. It is found that a Yld2000–3d plasticity model with isotropic strain hardening and thermal softening is suitable to describe the large deformation response, while a rate- and temperature-independent Hosford-Coulomb model is used to predict fracture. Impact experiments are performed on 4 mm thick targets with blunt, hemispherical and conical steel projectiles of 8 mm diameter and a mass of 13.8 g. The impact velocity is varied such that the full spectrum from the ballistic limit to complete penetration can be characterized. In addition, perpendicular and oblique configurations are considered. Numerical simulations are performed for all experiments confirming the validity of the identified constitutive model and providing unmatched insight into the dynamic penetration failure mechanism.